Increased Brachial Artery Compliance After Arteriovenous Fistula Creation as Measured by Shear Wave Elastography: Results From a Feasibility Study. (14th November 2019) - MacDonald, Conor‐James; Ross, Rose; Houston, John Graeme
Abstract : Objectives: Arterial stiffness has been proposed as a marker of arteriovenous fistula failure and can be measured locally by using ultrasound shear wave elastography (SWE). This preliminary study aimed to assess whether SWE measurements of the brachial artery were associated with arteriovenous fistula failure. Methods: Data were collected on patients who were indicated for fistula creation. Preoperative and postoperative vessel diameters from B‐mode ultrasound, brachial artery SWE maps, and demographic data were collected. Logistic and linear regression analyses were used to determine whether any of these variables were related to the outcome of the fistula 3 months after creation. Results: Data were acquired for 33 patients. Shear wave velocity values decreased after fistula creation (mean ± SD, –1.2 ± 1 m/s; P  < .05). No parameters were associated with failure of the fistula in the logistic regression analysis. Conclusions: No markers were related to fistula failure, but a decrease in the shear wave velocity was observed in the brachial arteries after fistula creation, indicating increased compliance.